2002
DOI: 10.1289/ehp.02110s2221
|View full text |Cite
|
Sign up to set email alerts
|

Lead sources, behaviors, and socioeconomic factors in relation to blood lead of native american and white children: a community-based assessment of a former mining area.

Abstract: Lead poisoning prevention requires knowledge of lead sources and of appropriate residential lead standards. Data are severely lacking on lead sources for Native American children, many of whom live in rural areas. Further, the relation of mining waste to blood lead concentrations (BPbs) of rural children is controversial. In collaboration with the eight tribes of northeastern Oklahoma, we assessed lead sources and their effects on BPbs for rural Native American and White children living in a former mining regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 43 publications
5
77
0
Order By: Relevance
“…Higher dermal levels were associated with males (SEX, male or female) and members of ethnic minorities (MINORITY, yes or no), consistent with disparities reported with blood lead concentrations in children (Malcoe et al, 2002). Residing in or near commercial areas (COMMERCIAL, yes or no), using gasoline-powered equipment (EQUIPMENT, yes or no), and not washing hands after using a lawnmower (LAW-NMOWER, yes, no, n/a) were also associated with higher dermal levels even though lead had been almost completely phased out of gasoline by 1996 (Pirkle et al, 1998), perhaps pointing to persistent contamination from previously available fuels.…”
Section: Multiple Regression Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…Higher dermal levels were associated with males (SEX, male or female) and members of ethnic minorities (MINORITY, yes or no), consistent with disparities reported with blood lead concentrations in children (Malcoe et al, 2002). Residing in or near commercial areas (COMMERCIAL, yes or no), using gasoline-powered equipment (EQUIPMENT, yes or no), and not washing hands after using a lawnmower (LAW-NMOWER, yes, no, n/a) were also associated with higher dermal levels even though lead had been almost completely phased out of gasoline by 1996 (Pirkle et al, 1998), perhaps pointing to persistent contamination from previously available fuels.…”
Section: Multiple Regression Analysissupporting
confidence: 79%
“…None of the other lead measurements (i.e., soil, indoor air, dust, dermal, food, or beverages) were found to be a significant predictor. Residential dust abatement was previously found to reduce childhood blood lead levels (Rhoads et al, 1999), but our study participants were largely adults, who generally do not exhibit the hand-to-mouth and pica behaviors common among children (Malcoe et al, 2002). The failure to detect a significant association of blood lead with lead in any environmental media suggests that the collection period for the exposure measurements was not long enough to reflect the long half-life of lead in the body.…”
Section: Multiple Regression Analysismentioning
confidence: 89%
“…Of the children tested, 21.4% lived in a former mining town. In a multivariate regression analysis, the investigators found that living in one of the former mining towns was associated with a 5.6 odds ratio (95% CI: 1.8-17.8) of having a blood lead >10 μg/dL even after adjusting for mean levels of lead in soil, floor dust, caregivers' education, and hand-to-mouth behaviors (31). Indices of lead paint (either exterior or interior) did not have a measurable impact on risk of elevated blood lead levels in this population.…”
Section: Metal Mixtures and Kids: Exposure And Dosementioning
confidence: 99%
“…Sixteen percent of mothers and nearly 10% of cord blood samples had PbBs >20 μg/dL (Al Khayat et al 1997b). Malcoe et al (2002) assessed lead sources and their effect on blood lead in rural Native American and white children living in a former mining region. Blood samples, residential environmental samples (soil, dust, paint, water) and caregiver interviews (hand-mouth behaviors, socioeconomic conditions) were obtained from a representative sample of 245 children ages 1-6.…”
Section: Potential For Human Exposurementioning
confidence: 99%